Influence of In‐Doping on the Structure and Electrochemical Performance of Compositionally Complex Garnet‐Type Solid Electrolytes - Alaa Alsawaf; Guruprakash Karkera; Thomas Diemant; Monaha Veerraju Kante; Yannik Schneider; Leonardo Velasco; Subramshu S. Bhattacharya; Florian Stainer; Martin Wilkening; Oliver Clemens; Jürgen Janek; Horst Hahn; et al. (Small Structures)
The electrochemical instability of electrode active materials as well as the flammability of the organic liquid electrolytes in Li‐ion batteries pose challenges for their safety and long cycle life. Solid electrolytes (SEs) that exhibit high ionic conductivity and a wide electrochemical stability window alleviate these challenges. Garnet‐type Li7La3Zr2O12 is a promising SE for next‐generation all‐solid‐state batteries. Herein, samples are prepared via a modified solid‐state reaction of compositionally complex Li6.3+zLa3Zr1.1−z Nb0.8Gd0.1InzO12 under different sintering atmospheres. X–ray diffraction patterns and Raman spectra prove the formation of a cubic garnet structure. Significant morphological changes are detected upon In‐doping and correlated to the ionic conductivity. The total Li‐ion conductivity of the dense pellets reaches 1 mS cm−1, among the highest reported to date, with an activation energy of 0.38 eV for the macroscopic ion transport obtained by impedance spectroscopy and as low as 0.24 eV for local Li‐ion hopping processes determined by 7Li nuclear magnetic resonance spin‐lattice relaxation measurements. The electronic contribution to the conductivity is negligible (10−10 S cm−1) making this compositionally complex SE a suitable candidate for all‐solid‐state battery applications.